2006
DOI: 10.1175/jcli3789.1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Sources of U.S. Seasonal Forecast Skill

Abstract: In this study the authors diagnose the sources for the contiguous U.S. seasonal forecast skill that are related to sea surface temperature (SST) variations using a combination of dynamical and empirical methods. The dynamical methods include ensemble simulations with four atmospheric general circulation models (AGCMs) forced by observed monthly global SSTs from 1950 to 1999, and ensemble AGCM experiments forced by idealized SST anomalies. The empirical methods involve a suite of reductions of the AGCM simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 30 publications
5
79
0
Order By: Relevance
“…In other words, the dynamical forecast skill above persistence for 28-year hindcasts is largely captured by using dynamical forecasts for the 10 strongest ENSO events (1983,1987,1988,1989,1992,1998,1999,2000,2003,2008) and persistence forecasts for the other 18 years. This finding is consistent with previous studies that identify ENSO variability as the primary driver of seasonal predictability in air temperature and precipitation anomalies over the continental United States (Barnett and Preisendorfer 1987;Quan et al 2006). However, it should be noted that there is residual skill in the dynamical forecast beyond that generated during ENSO events, particularly for long lead forecasts (cf., left and middle panels of Fig.…”
Section: Mechanisms Of Sst Predictabilitysupporting
confidence: 93%
See 1 more Smart Citation
“…In other words, the dynamical forecast skill above persistence for 28-year hindcasts is largely captured by using dynamical forecasts for the 10 strongest ENSO events (1983,1987,1988,1989,1992,1998,1999,2000,2003,2008) and persistence forecasts for the other 18 years. This finding is consistent with previous studies that identify ENSO variability as the primary driver of seasonal predictability in air temperature and precipitation anomalies over the continental United States (Barnett and Preisendorfer 1987;Quan et al 2006). However, it should be noted that there is residual skill in the dynamical forecast beyond that generated during ENSO events, particularly for long lead forecasts (cf., left and middle panels of Fig.…”
Section: Mechanisms Of Sst Predictabilitysupporting
confidence: 93%
“…The difficulty of accurately forecasting winds on seasonal timescales is not surprising given the chaotic nature and short memory of the atmosphere (Goddard et al 2001), though our findings do suggest promise at least when climate signals are large. Prior studies demonstrating ENSO variability as the primary driver of forecast skill for air temperatures and precipitation over the US continent (Barnett and Preisendorfer 1987;Quan et al 2006) have motivated consideration of conditional forecasts based on the ENSO state (Pegion and Kumar 2013), and a similar approach may be fruitful for SST forecasts off the US west coast.…”
Section: Sst Forecast Skill In the Ccsmentioning
confidence: 99%
“…These hindcast experiments have been used to globally analyze the predictability at seasonal time scales, especially in areas influenced by ENSO activity (Palmer et al 2004;Gutiérrez et al 2005). Moreover, although the potential predictability is lower at extratropical latitudes, recent studies have shown certain skill in those regions (e.g., in North America) associated with ENSO teleconnections (see, e.g., Quan et al 2006), and also with other sources of seasonal predictability, such as the persistence of the North Pacific decadal oscillation (Gershunov and Cayan 2003) or the moisture content (Wang and Kumar 1998;Douville 2004). However, in most of the extratropics, the signals predicted by general circulation models are weak and do not add valuable information over a climatological forecast.…”
Section: Introductionmentioning
confidence: 99%
“…ENSO has been shown to influence precipitation and streamflow in Central Texas (Gershunov 1998;Rajagopalan and Cooke 2000;Watkins and O'Connell 2005;Slade and Chow 2011;Vicente-Serrano et al 2011;Wei and Watkins 2011;Anderson and Rose 2012). The ability to predict ENSO has been improving with statistical and dynamic models (Quan et al 2006;Barnston et al 2012;. A more in-depth discussion of the model's use of ENSO ensemble forecasts can be found in Anderson et al (2015).…”
Section: Model Development and Updatesmentioning
confidence: 99%